The relational context of employee engagement: an intrinsic perspective - Smith, Christine L., author; Byrne, Zinta S., advisor; Gibbons, Alyssa, committee member; Vacha-Haase, Tammi, committee member; Cross, Jennifer, committee member (Colorado State University. Libraries, 2014)
The purpose of the current study was to expand on the existing understanding of the relational context of employee engagement. Previous studies and theories applied to understanding the relational context of work and employee engagement have predominately adopted an instrumental perspective of relationships. An instrumental perspective of relationships assumes individuals engage in relationships (and benefit from them) because the relationship is a means to an end, with the end being some other reason such as task-related support, power, influence, or other extrinsic reasons. Conversely, an intrinsic perspective of relationships views them as beneficial due to the inherent enjoyment, interest, and holistic wellbeing individuals experience as a result of their interactions. Based on an intrinsic perspective of relationships, grounded in self-determination theory, this study tests the notion that the quality of work relationships is an important consideration for more fully understanding the relational context of employee engagement. Data collected from 364 working adults, across diverse industries and occupations, revealed that leader relationship quality (intrinsic perspective) is a stronger predictor of employee engagement than leader support (instrumental perspective), thereby supporting the argument that the previous focus of engagement research (i.e., mainly adopting an instrumental perspective of relationships) is incomplete. Additionally, results showed that coworker relationship quality (relative to leader relationship quality) is a stronger predictor of satisfaction of relatedness needs at work. Overall, the results of this study suggest there is value in examining an intrinsic perspective of relationships in regards to engagement.
Keywords: coworkers; work relationships; leadership; employee engagement